Cultivating Resilience: Key-Messages from the first Mediterranean Conservation Agriculture Conference - Ouerghemmi, Hassen; Shiri, Zahra; Monti, Andrea; Schoeber, Mia; Rinaldi, Michele; Cicek, Harun (ConServe Terra Project, 2024)
The Mediterranean Conference on Conservation Agriculture (CA), held in Tunis on 23-24 November 2023, aimed to address the challenges of CA adoption in the region. Organized by the EU-funded PRIMA projects, ICARDA and INRAT, the conference highlighted the role of CA in addressing climate change and soil depletion. However, there are challenges to CA such as social prejudices, lack of knowledge and lack of political will. Presentations and discussions focused on strategies for farmers, scientists and policy makers, emphasizing the need to implement massive changes and work together to keep CA from being a dream. The conference was about adopting CA back practices as one of the ingredients to improve resilience to climate change and sustainable agriculture.